Analysis of Educational Value in the Folklore of the Legend of the Crying Stone and the Learning Implementation Plan in Class V of Elementary School - Retno Ely Kartika; Suyoto Suyoto; Muflikhul Khaq (CV. Rayyan Dwi Bharata, 2023)
This study aims to describe: (1) intrinsic elements; (2) educational value in folklore Legend of the Crying Stone; and (3) plans for implementing learning in class V SD. The data source for this research is the folklore of the Legend of the Crying Stone. This research procedure uses a qualitative approach in which the data reveals a problem, situation or event. The focus of this research is educational values including: religious, moral, and social values. The collection of research data was carried out using library techniques, reading techniques, and note-taking techniques. The research instrument is the author himself as a researcher. The data analysis technique was carried out using content analysis techniques. Presentation of the results of the analysis used informal presentation techniques. The results of the study can be concluded that: (1) the intrinsic elements of folklore are: (a) theme: rebellious child; (b) setting/setting: setting: on the hill, on the road, at home, and at the market, setting: in the morning, setting: sad and tense; (c) characters and characterizations: the main character Mak Dasah is patient and friendly while Darmi is lazy and arrogant, additional characters: Wak Sahid has a friendly nature; (d) groove: forward; (e) the mandate: never be disobedient to your parents and hurt them; (2) the value of education consists of: (a) the value of religious education includes: praying to God, and God's power; (b) the value of moral education includes: hard work and patience; (c) the value of social education, namely affection in the family; (3) the implementation plan of learning in class V SD based on basic competence 1.2 identify elements of stories about folklore that are heard using cooperative learning type of group investigation (group investigation). Students carry out the following activities: preliminary activities; core activities include: identifying topics, planning learning assignments, carrying out investigations, preparing final reports, and presenting report results; closing.